Relationship of board density and resin contents towards the particleboard properties from weathered oil palm trunk / Jamaludin Kasim ...[et al.] - Kasim, Jamaludin; Che Kar, Muhamad Nasrulrahman; Wan Abd Rahman, Wan Mohd Nazri; Ahmad, Nurrohana; Sarmin, Siti Noorbaini; Mohd Yunus, Nur Yuziah; Mansor, Rafizah (2013)
In this study, the relationship of density and resin content (RC) on mechanical and physical properties of particleboard manufactured from weathered oil palm trunk particles were determined Weathered trunk of Oil palm (Elaeis guineensis Jacq.) was used as alternative raw materials for particleboard manufacturing. During board manufacture, resin content (7, 9 and 11%) and density (500, 600 and 700kg/m3) were used The experimental panels were tested for their mechanical strength including modulus of rapture (MOR), modulus of elasticity (MOE), internal bonding (IB) and physical properties thickness swelling (TS) and water absorption (WA) were determine based on British European (BS EN) standard Mechanical properties and physical properties strength of particleboard increased toward higher board density and resin contents. All of particleboard does not satisfy the minimum MOR, MOE, IB and TS standard requirement of non-load bearing particleboards for general use.